BIBLIOMETRIC ANALYSIS OF LEARNING MODELS RESEARCH USING VOSVIEWER - Elyakim Nova Supriyedi Patty; Sri Astuti Iriyani (Sean Institute, 2023)
This study aims to analyze and demonstrate step-by-step bibliometric data analysis using VOSViewer systematically. Step-by-step analysis is provided to make first-time users accessible easier to use VOSViewers. So that learning models can be combined with other areas to study. This study presents data analysis on learning models and their development over the course of ten years (2013–2022) using mapping tools in VOSViewer. The method used is qualitative descriptive to describe the performance of bibliometric analysis by generating a network visualization of the selected topic. From the search results, 999 relevant published journals were found, starting from 2013–2022, which were then grouped into 10 categories according to the year of issue. After grouping journal data, we found that the most published articles in 2015-2020. There are many opportunities to discover new things on this topic. This study is expected to serve as a direction for authors who conduct research and determination of research themes.